Performance of Food Production and some Marketing Issues in India - Kumar, Parveen; Kundu, K. K.; Suhag, K. S. (Indian Journal of Marketing, 2005)
India, with geographical area of 329 million hectare is the seventh largest country in the world. The total population of the country has crossed one billion marks recently. Agriculture is the mainstay of Indian Economy. It provides livelihood to three fourth of its population and contributes about 20 per cent of the total value of country's exports. The agricultural economy has witnessed profound changes during successive decades of planning, more particularly in the wake of new agricultural strategies adopted in the mid-60s. Appropriate policy support for capital investment in agriculture, including creation of required infrastructure, building of a strong agricultural research and education system coupled with an extension system had helped in achieving food security despite growing population.